2014
DOI: 10.1016/j.ajic.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of nasal Staphylococcus aureus carriage in health care professionals by treatment with a nonantibiotic, alcohol-based nasal antiseptic

Abstract: Nasal application of a nonantibiotic, alcohol-based antiseptic was effective in reducing S aureus and total bacterial carriage, suggesting the usefulness of this approach as a safe, effective, and convenient alternative to antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Most alcoholbased hand antiseptics contain either isopropanol or ethanol (86). Steed et al (87) recently published a double-blinded, placebocontrolled RCT testing the effectiveness of an alcohol-based nasal antiseptic in reducing S. aureus nasal colonization in colonized health care workers. Health care workers testing positive for nasal S. aureus colonization were treated three times during the day with a nasal alcohol-based antiseptic or placebo.…”
Section: Alcohol-based Nasal Antisepticmentioning
confidence: 99%
“…Most alcoholbased hand antiseptics contain either isopropanol or ethanol (86). Steed et al (87) recently published a double-blinded, placebocontrolled RCT testing the effectiveness of an alcohol-based nasal antiseptic in reducing S. aureus nasal colonization in colonized health care workers. Health care workers testing positive for nasal S. aureus colonization were treated three times during the day with a nasal alcohol-based antiseptic or placebo.…”
Section: Alcohol-based Nasal Antisepticmentioning
confidence: 99%
“…An alternative to nasal decolonization is the use of an antiseptic such as 5% povidone‐iodine 13,16‐18 or an alcohol‐based antiseptic (eg, 70% ethanol) 19,20 . Use of an antiseptic may be advantageous for universal decolonization because there is less concern for antibiotic resistance.…”
Section: Continuing Education: Clinical Issuesmentioning
confidence: 99%
“…Researchers found that mean infection rates were reduced 81% when compared with the baseline period before the intervention 19 . In another study on alcohol‐based nasal antiseptics, Steed et al 20 found that S aureus and total bacterial carriage were effectively reduced in health care personnel who underwent nasal decolonization with the nasal antiseptic. Additional research is needed to evaluate the effects of personnel nasal decolonization and postoperative patient and caregiver nasal decolonization on the patient's SSI outcomes.…”
Section: Continuing Education: Clinical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant source of nosocomial infection was proposed to be the nasal carriage of S. aureus among the health care personnel. The carriage rates were found to vary from 20-40% [4,5].…”
Section: Introductionmentioning
confidence: 99%